2016
DOI: 10.1371/journal.pone.0148422
|View full text |Cite
|
Sign up to set email alerts
|

A New Glabrous Gene (csgl3) Identified in Trichome Development in Cucumber (Cucumis sativus L.)

Abstract: Spines or trichomes on the fruit of cucumbers enhance their commercial value in China. In addition, glabrous mutants exhibit resistance to aphids and therefore their use by growers can reduce pesticide residues. Previous studies have reported two glabrous mutant plants containing the genes, csgl1 and csgl2. In the present study, a new glabrous mutant, NCG157, was identified showing a gene interaction effect with csgl1 and csgl2. This mutant showed the glabrous character on stems, leaves, tendrils, receptacles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…This hypothesis was supported by data from the present study, with no observed difference in leaf trichome density but a significant difference in fruit spine density between fs1 and WT (Fig. Neighbor-joining phylogenetic tree was generated after a complete protein sequence alignment with Clustal X (1.81) Table 3 of trichomes on foliage or fruit were mapped on chromosomes 2, 3 and 6, respectively (Yang et al 2011;Li et al 2015;Pan et al 2015;Wang et al 2016;Zhao et al 2015;Cui et al 2016). In cucumber, a number of genes related to fruit spines have been identified: B for black spine, ns for numerous spines, ss for small spines, s or s1 for spine size and frequency, s2 and s3 for dense and small spines, and gl (glabrous) and tril (trichome-less) for trichomes formation (Call and Wehner 2010;Wang et al 2016).…”
Section: Inheritance and Domestication Of Fruit Spine Density Trait Isupporting
confidence: 79%
See 3 more Smart Citations
“…This hypothesis was supported by data from the present study, with no observed difference in leaf trichome density but a significant difference in fruit spine density between fs1 and WT (Fig. Neighbor-joining phylogenetic tree was generated after a complete protein sequence alignment with Clustal X (1.81) Table 3 of trichomes on foliage or fruit were mapped on chromosomes 2, 3 and 6, respectively (Yang et al 2011;Li et al 2015;Pan et al 2015;Wang et al 2016;Zhao et al 2015;Cui et al 2016). In cucumber, a number of genes related to fruit spines have been identified: B for black spine, ns for numerous spines, ss for small spines, s or s1 for spine size and frequency, s2 and s3 for dense and small spines, and gl (glabrous) and tril (trichome-less) for trichomes formation (Call and Wehner 2010;Wang et al 2016).…”
Section: Inheritance and Domestication Of Fruit Spine Density Trait Isupporting
confidence: 79%
“…2c, d), which might cause increased expression level of CsH-DZIV11 in the fs1 mutant (Fig. Interestingly, CsHDZIV11 in this study, TRIL/CsGL3 found by Wang et al (2016), Pan et al (2015) and Cui et al (2016) are the same gene, Csa6M514870. 4).…”
Section: Hd-zip IV Gene Cshdziv11 Might Be the Best Candidate Gene Fomentioning
confidence: 55%
See 2 more Smart Citations
“…Five trichome-related mutants of the genes CsGL3, TRIL, MICT, TBH, and CsGL1, all of them encoding homeodomain-Leu zipper transcription factors from different subfamilies, have been reported in C. sativus (Chen et al, 2014;Li et al, 2015;Pan et al, 2015;Zhao et al, 2015;Cui et al, 2016;Wang et al, 2016b). Based on the observed phenotypes, a molecular mechanism underlying the development of multicellular trichomes in this species has been proposed in a recent review and seems to confirm that the transcriptional control of multicellular trichomes in C. sativus differs from the one observed in Arabidopsis.…”
Section: A Detailed Understanding Of Glandular Trichome Initiation Anmentioning
confidence: 99%